Seven challenges that shaped the New Testament: understanding the inherent tensions of early Christian faith - Spencer, Franklin Scott (Baker Academic, 2024)
A senior New Testament scholar investigates seven critical areas of tension--historical, moral, political, material, social, perceptual, and temporal--that shape the "big ideas" set forth in the New Testament.